Use of Dental Stem Cells Harvested from a Tooth or Follicle (Global Journal of Medical Research, 2018)
Regenerative medicine is gaining popularity and inspires dentists to follow evidence-based literature for educating the parents about collecting, storing, sustainability and utility of dental stem cells about autologous regenerative therapies. Stem cells are present intrinsically in the apical papilla or dental pulp cells for treatment associated to regenerative endodontics.